Egg quality and isoflavone deposition due to dietary inclusion of isoflavone soy sauce by-product (ISSBP) in laying hens - Malik, A.; Suprijatna, E.; Yunianto, V. D.; Mahfudz, L. D.; Suthama, N. (Diponegoro University, 2019)
The objective of the study was to evaluate the quality and deposition of isoflavones in the egg due to dietary inclusion of isoflavone soy sauce by-product (ISSBP) in laying hens. Experimental animals were 480 birds of 20-week old laying hens of Isa Brown strain, with initial body weight of 1,754 ± 42 g. The experiment was arranged in a completely randomized design (CRD), with four treatments and six replications (20 birds each). The treatments were dietary inclusion levels of isoflavone soy sauce by-product as follows: ISSBP0 = without isoflavones, ISSBP40 = 40 mg/100g, ISSBP80 = 80 mg/100g, and ISSBP120 = 120 mg/100 g feed. Dietary treatments were given for 10 weeks from week 20 until 30-week old. Parameters observed were egg cholesterol and isoflavone isomers in feed, blood, and eggs. Data of total cholesterol and isoflavone in the egg were statistically analysed and isoflavone isomer concentration in feed, blood, and egg were descriptively described. The results showed that feeding ISSBP significantly (P <0.05) decreased cholesterol and increased isoflavones in egg. Total cholesterol content in egg decreased up to 33.8%. However, isoflavones in the yolk were higher (28.9 mg/g) than those in blood (13.75 mg/g), and those deposited into the yolks indicated better quality because containing more aglicons isomers (87.5%), than those in feed (52%) and blood (68.4%). In conclusion, dietary inclusion of ISSBP to laying hens’s decreased cholesterol content and increased isoflavones deposition into the egg with better quality, so that the eggs can function as functional food.